Efficacy and tolerability of BP-C1 in metastatic breast cancer: A Phase II, randomized, double-blind, and placebo-controlled Thai multi-center study - Kritiya Butthongkomvong (2020)
© 2019 Butthongkomvong et al. Aims: The aim of this study was to compare the efficacy and tolerability of BP-C1 vs equallooking placebo in metastatic breast cancer. Materials and methods: A randomized, double-blind, placebo-controlled multi-center study with a semicross-over design was performed. Sixteen patients received daily intramuscular injection of 0.035 mg/kg bodyweight of BP-C1 and 15 patients received equal-looking placebo for 32 days. After 32 days, the placebo patients crossed to BP-C1 with the last observation in the placebo period as baseline. The status of receptors including estrogen receptor (ER), progesterone receptor (PtR), and human EGF receptor 2 (HER2) was analyzed prior to inclusion in the study. Thoracoabdominal CT scan was blindly analyzed by the same independent radiologist in accordance with the RECIST criteria 1.1. Toxicity was assessed according to the NCI Bethesda Version 2.0 (CTC-NCI), and the quality of life (QOL) was assessed according to European Organization for the Research and Treatment of Cancer QOL-C30 and QOL-BR23. Results: The sum of target lesion diameters (sum lesions) after 32 days of treatment increased by 8.9% (P=0.08) in the BP-C1 arm compared to 37.6% (P<0.001) in placebo patients. Twelve of the 15 placebo patients subsequently had BP-C1 treatment. The increase in sum lesions was 3.5% in these patients. The sum of CTC-NCI was increased 18.7% in the BP-C1 arm (P=0.38) compared to 50.9% (P=0.04) in placebo patients. Four mild/moderate adverse events (AEs) present in BP-C1. Two mild/moderate AEs and one severe AE present in placebo. The QOL benchmarks “breast cancer problems last week”, “sexual interest and activity last 4 weeks”, and “breast cancer-related pain and discomfort last week” were stable in the BP-C1 arm but deteriorated in placebo patients. The sum lesions increased significantly in ER+ (P=0.02) and PtR+ (P=0.03) but not in HER2+. The increase in sum lesions significantly decreased (P=0.02) with an increasing number of negative receptors. Conclusion: A total of 32 days of BP-C1 treatment inhibited cancer growth and was well tolerated with few and mainly mild AEs. The efficacy of BP-C1 was superior in receptor-negative patients.